Does Coastal Community Need Takaful Protection From Coastal Erosion? - Fauzilah, Salleh; Nurfarhana, Ahmad Saufi (2018)
Coastal erosion is one of natural disasters which results in critical destruction to both environment and community. Not only that, components of the environment will also be negatively affected by this. The higher the severity of this phenomenon, there will be more degradation in flora and fauna in terms of quality and quantity. Simultaneously, the socio-economic activities of the coastal community will be disrupted. In this study, the negative outcome which should be emphasized is the financial burdens posed on individuals. Therefore, associated study was conducted with the purpose to optimize the hostess communities’ welfare through minimum financial burdens during the occurrence of coastal erosion. The survey was conducted on the coastal community whose households received the most impact from the disaster along the entire coastline of Peninsular Malaysia, so that information regarding the overall amount of loss or damaged costs sustained when this disaster occurred could be collected. Besides, in order to investigate on the suitability of Takaful scheme, the coverage scheme, premium charge and ratio of compensation, focus group discussion (FGD) was a group among related agencies who was involved in this study.